MOTIVASI PETANI DALAM USAHATANI PADI SAWAH MASA KINI (Studi Kasus di Desa Sukaharja dan Desa Sukamulih Kecamatan Sariwangi Kabupaten Tasikmalaya) - Yayat Sukayat; Ganjar Kurnia; Iwan Setiawan; Ukas Suarfaputra (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
Historically, Tasikmalaya Regency is the embryo of the development of lowland rice in eastern Indonesia. Since the 7th century, rice culture has been institutionalized in the lake community, strengthened by the printing of the first rice fields in Sukapura in the 17th century by Regent Wiradadahan. In its development (at the present time), paddy fields continue to decrease, most recently in 2018 an area of 4023 hectares has been converted. However, the number of farmer households using agricultural land, increased by 3.02% and RTP Gurem increased by 3.88%, even the number of farmers increased by 49.60%. This phenomenon indicates the dependence of the Tasikmalaya community on the rice field farming sector. The question is what is the motivation of farmers in lowland rice farming. The purpose of this study was to determine the motivation of farmers in lowland rice farming. This research used a qualitative method with a case study technique. The technique of determining informants was carried out deliberately. Data collection techniques were carried out by in-depth interviews, observation and FGD. Data analysis was carried out by means of data reduction, data display, and conclusions. The result of their research on their motivation to do business is social motivation to maintain self-existence, without neglecting economic motivation.